Key point is knowing that

sin(pi x) = -sin(x)

cos(pi x) = -cos(x)

tan(4/3) = sin(4/3)/cos(4/3) = sin( /3)/cos( /3) = [-sin(/3)]/[-cos(/3)]

= sin(/3)/cos(/3) = (3/2) / (1/2) = 3

Key point is knowing that

sin(pi x) = -sin(x)

cos(pi x) = -cos(x)

Key point is knowing that

sin(pi x) = -sin(x)

cos(pi x) = -cos(x)

tan(4/3) = sin(4/3)/cos(4/3) = sin( /3)/cos( /3) = [-sin(/3)]/[-cos(/3)]

= sin(/3)/cos(/3) = (3/2) / (1/2) = 3

This post is last updated on hrtanswers.com at Date : 1st of September – 2022